- The impact of the challenges faced by the expatriate human resources of the multinational companies to retain them - Applied study - Al Balushi, Issam bin Ali bin Mousa (Journal of Economic, Administrative and Legal Sciences, 2018)
This thesis focuses on analyzing the most important challenges facing expatriate human resources in multinational companies, and the most important methods that human resources departments deal with in order to maintain them. The study questions and hypotheses that aim to reach the relationship and impact results include the challenges faced by expatriate workers, In order to reach fruitful results in this field, and to enhance the chances of success of expatriates through the development of policies and programs for the care of expatriate human resources on the ground. This is the first letter of its kind in the Arab world according to the researcher’s knowledge and Under the Supervised. The researcher conducted a survey on a sample of 70 expatriate employees in the Sultanate of Oman. To identify the most important challenges facing them in the country of expatriation. And take them to be the nucleus of the final questionnaire, which was distributed to the main sample under study. The sample of the study consisted of (400) expatriate employees, where the number of retrieved and excluded forms (15) form, and therefore the number of questionable forms (385) form, and the percentage of questionable forms (96.3%). The researcher relied on the design of the questionnaire list and the five-dimensional Likert scale was used to measure respondents’ responses to the questionnaires, filtered and classified to facilitate the analysis process, to draw conclusions and indicators of them on the subject of study using appropriate statistical methods consistent with the assumptions. The following statistical methods were used (medium - deviation - standard - coefficient of variation - relative importance) Alpha-cronbach coefficients (persistence) Honest coefficients, internal consistency, simple linear regression, linear regression analysis and artificial neural networks, path analysis.